A Research of The Impact of Strategic Alliance Co-operation Model on Brand Competitiveness - The Case of LEGO - Zhou, Lun (Transactions on Economics, Business and Management Research, 2024)
With the development of the global economy and the advancement of science and technology, the fragmentation of knowledge is increasing, resulting in the fact that no single enterprise can solve technological challenges on its own. In this regard, enterprises need to work together to overcome technological challenges cooperatively to achieve a win-win situation. Strategic alliances are an organisation between firms and the market that facilitates co-operation between firms and promotes risk sharing and benefit sharing. By engaging in strategic alliances, enterprises are able to facilitate the upgrading of their products and services, as well as enhance their brand image. Consequently, strategic alliances are increasingly becoming a prevalent development approach for various enterprises to keep abreast with the trends of the times. This research takes LEGO as the research object, through analysing LEGO's participation in strategic alliances in recent years, it explores the impact of strategic alliance co-operation on LEGO's product upgrading and business optimization. Based on the analysis of LEGO's strategic alliances, it proposes specific ideas to improve brand competitiveness. The purpose is to provide suggestions for enterprises to participate in strategic alliances, and then to build the brand effect of enterprises to inspire.